2010
DOI: 10.1111/j.1651-2227.2010.01868.x
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil in neonatal intensive care and anaesthesia practice

Abstract: Remifentanil seems to be an effective and safely used opioid for neonatal intensive care and anaesthesia practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 55 publications
(75 reference statements)
2
32
2
Order By: Relevance
“…The ineffectiveness of remifentanil at these doses is in contrast with the potent effect of this opioid described in previous studies [3,4,5,6]. It has been suggested that there may be a dose effect for the occurrence of chest wall rigidity associated with remifentanil [2,7]. To better understand the link between high doses of remifentanil and the observed insufficient sedation, we believe it would have been relevant to provide the interval duration between each injection.…”
contrasting
confidence: 51%
“…The ineffectiveness of remifentanil at these doses is in contrast with the potent effect of this opioid described in previous studies [3,4,5,6]. It has been suggested that there may be a dose effect for the occurrence of chest wall rigidity associated with remifentanil [2,7]. To better understand the link between high doses of remifentanil and the observed insufficient sedation, we believe it would have been relevant to provide the interval duration between each injection.…”
contrasting
confidence: 51%
“…Our anecdotal experiences in past years suggest that even sick neonates will reasonably tolerate higher doses of remifentanil in terms of hemodynamic stability. Emergence from high-dose remifentanil anesthesia seems to be within a predictable range in neonatal patients, as reported in previous studies [6]. Patients receiving l-opioid receptor agonists may occasionally exhibit muscle rigidity at higher doses, which may result in difficult positive pressure ventilation, and intense muscle relaxation would be required for high-dose opioid anesthesia.…”
supporting
confidence: 71%
“…Currently, remifentanil, which is a newer, ultra-short-acting opioid, is another potentially useful choice if the neonatal patients are to be extubated at the end of surgery. The pharmacokinetics of remifentanil seem to be predictable even in neonates [6]. Limited pharmacokinetic data in the neonatal population may provide a useful dosing guide for remifentanil.…”
mentioning
confidence: 99%
“…This characteristic has obvious advantages in anesthesia and sedation practice. Indeed, the role of remifentanil in pediatric anesthesia and intensive care has been reviewed recently [ 90 ].…”
Section: Remifentanilmentioning
confidence: 99%